Raising awareness of monitoring systems in the workplace - Kyprianou, Nicholas (2013)
The exponential technological growth of ubiquitous and pervasive computing gave the opportunity to employers all over the world to apply surveillance at their businesses and collect various information about their employees. The problem with this trend is the lack of knowledge of the existence of monitoring systems on behalf of the employees, which subsequently does not allow them to benefit from any potential advantages of such technology and even worse violates some of their privacy rights. The aim of this project is to raise awareness of monitoring systems in the workplace through the design of a mobile application. In an attempt to give this application an innovative nature, aspects from a number of research topics like sousveillance, gamification and crowd sourcing were combined to produce the final design of the application. Hence, research on selected topics will be shown in the report, alongside the methods for eliciting user requirements through a participatory design approach. Also the process of designing the application and the implementation of features will be showed, which were evaluated through field trials from potential users. Finally, discussion on the succession of the project will be followed by the conclusions and possible improvements that can occur in the future. In terms of the findings, this project managed one iteration of the process described throughout the report, however even from only this iteration results obtained are encouraging. The user driven approach that was adopted in some key stages of the project, helped to arrive in some interesting conclusions. These conclusions alongside the responses and results obtained, suggest that repeating this process a few more times will make the proposed mobile application the stepping stone to raising awareness - not limited only in the context of work - through such mobile applications.